Post-process steam pasteurization of packaged Frankfurters combined with acid/buffer treatments for control of Listeria monocytogenes - Reicks, A.L.; Thippareddi, H.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The efficacy of a saturated steam-based post-process pasteurization system to reduce/ eliminate Listeria monocytogenes on frankfurters was evaluated. Frankfurters were packaged individually or in a single layer format (4 per package, touching). Samples were surface treated with 2% lactic acid, 4% lactic acid, 2% buffered sodium citrate, or 2% buffered sodium lactate, vacuum packaged, and steam pasteurized to end-point surface temperatures of 160, 170 or 180°F using a Townsend Post-Process Pasteurization system (formerly Stork-RMS Protecon). Pasteurization of inoculated single layer franks to surface end point temperature targets of 160, 170, and 180°F resulted in L. monocytogenes reductions (P<0.05) of 0.92, 1.44 and 2.89 log colony forming units (CFU)/frank, respectively. Greater reductions in L. monocytogenes populations were observed for individually packaged frankfurters with 2.32, 4.62 and 6.52 log CFU/frank reductions at target surface end point temperatures of 160, 170, and 180°F, respectively. No differences (P>0.05) were noted between various surface acid treatments applied. Post-process pasteurization of frankfurters (in-package) using the saturated-steambased Townsend system was effective in reducing numbers of L. monocytogenes.
Keywords: Beef; Steam pasteurization; Frankfurters; Listeria monocytogenes